The Use of SASAMBO Culture in Learning Natural Product Chemistry to Support Traditional Health Tourism in Lombok and Sumbawa Islands - Aliefman Hakim; Jamaluddin Jamaluddin; Syarifa Wahidah Al Idrus; Muhammad Eka Putra Ramandha (Postgraduate, University of Mataram, 2020)
The SASAMBO (Sasak, Samawa, Mbojo) tribe has a variety of medicinal plants. The abundance of SASAMBO tribal medicinal plants can be used in learning the natural product chemistry which are expected to support traditional health tourism on the islands of Lombok and Sumbawa. Natural product chemistry examines the chemical content associated with the efficacy of a medicinal plant. This linkage can provide scientific support for the use of SASAMBO traditional medicinal plants. The method used in this research is the study of literature and questionnaires. Data sources came from public records, the results of questionnaire responses, and scientific articles related to SASAMBO traditional medicine. The results showed that there were various SASAMBO medicinal plants which were potentially used in the study of natural product chemistry with details, Lombok (Sasak) 43 species, Sumbawa (Samawa) 25 species, and Bima (Mbojo) 35 species. Some of these plant species are used for the treatment of diseases caused by viruses, so it has the potential to be used to treat corona outbreaks. Lombok and Sumbawa islands have abundant medicinal plants, this makes the two islands potential as a traditional health tourism destination.